Turkey - National Innovation and Technology System : Recent Progress and Ongoing Challenges - World Bank (Washington, DC, 2014)
In January 2008, the Turkish Government requested the World Bank to jointly undertake an assessment of its National Innovation System (NIS) in order to help guide its ongoing efforts to deepen the role of innovation in the Turkish economy. This report identifies the recent progress and key ongoing challenges facing Turkey's NIS and draws on international experience to outline potential issues for further analysis. The next section provides an overview of the institutional structure, policy framework and main programs of Turkey's NIS and identifies issues in three main areas that hinder innovation performance: the intellectual property right (IPR) regime, collaboration between the research and enterprise sectors, and innovation finance. The third section uses available information (aggregate and firm-level data and a set of 20 case studies) to provide a review of the innovation and technology performance of the enterprise sector in Turkey and preliminarily address its possible determinants. Areas for further potential study and analysis are identified based on the key findings in each section.